Assessing the Contribution of Family Physicians in Preoperative Risk Assessment and Postoperative Management of Surgical Patients - Alrashidi, Abdullah Salih; Alasmari, Hassan Dhafer; Alqarni, Naif Saeed; Asiri, Abdullah Ibrahim; Alanzi, Khalid Mubarak; N Alqahtani, Yousif Abdulrahman; Kurdi, Faisal Nasser; Alotaibi, Anas Nahes; M Alqarni, Mohammed Dhafer; Asiri, Abdullah Ibrahim (Journal of Neonatal Surgery, 2025)
Background: Family physicians play a crucial role in the surgical care continuum, particularly in preoperative risk assessment and postoperative management. Their comprehensive understanding of patients' medical histories and overall health status positions them uniquely to contribute to optimizing surgical outcomes. Despite their critical involvement, the impact of family physicians' contributions in these areas remains underexplored. Methodology: This study aimed to assess the knowledge and practices of family physicians concerning preoperative risk assessment and postoperative management through a cross-sectional survey. A structured questionnaire was distributed to a representative sample of 150 family physicians across multiple primary healthcare centers. The survey evaluated physicians' awareness of preoperative risk factors, adherence to assessment guidelines, and postoperative management practices. Data were analyzed using descriptive and inferential statistics. Results: The study revealed that 84.7% of physicians recognized diabetes mellitus as a preoperative risk factor, with 80% routinely using risk stratification tools. However, only 60% consistently adhered to established preoperative guidelines. In postoperative care, 90% of physicians followed up within the recommended timeframe, and 85% demonstrated good knowledge of postoperative care guidelines. Significant associations were found between years of experience and knowledge of preoperative risk factors, with more experienced physicians showing higher adherence to best practices. Conclusion: While family physicians generally exhibit strong knowledge in preoperative risk assessment and postoperative management, there are notable gaps in the consistent application of guidelines and the balance between standardized protocols and individualized care. Addressing these gaps through targeted training, updates on clinical guidelines, and research into management strategies could enhance the quality of surgical care and improve patient outcomes.